Ανίχνευση του Mycobacterium avium subspecies paratuberculosis σε βρεφικές φόρμουλες βασισμένες στο γάλα με τη χρήση καλλιέργειας και με τη μέθοδο της PCR - Χριστοδούλου, Μαρίτσα (Τμήμα Γεωπονικών Επιστημών,Βιοτεχνολογίας και Τεχνολογίας Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος/Faculty of Geotechnical Sciences and Environmental Management, 2012)
Mycobacterium avium subspecies paratuberculosis is the causative agent of Johne’s disease in ruminants. Accumulating data supports a positive correlation between the presence of MAP and the development of Crohn’s disease in humans. MAP is a very persistent organism which can be present in milk and milk products surviving pasteurisation. The purpose of this study was to investigate the possibility of MAP’s presence in infant milk formulas, by implementing both conventional culture on Herrold’s Egg Yolk Medium and also direct PCR detection. A total of 35 samples from 11 different producers were analyzed. MAP was cultured from three samples (8,6%) following a six month incubation period whereas seven of the samples (21,9%) were direct IS900 PCR positive for MAP. The presence of MAP in infant formulas highlights the need to decrease the risk of exposure for infants and young children, by assuring that skim-milk intended for the manufacture of formulas is from MAP-free herds.
Keywords: Paratuberculosis; Ruminants; Παραφυματίωση; Μηρυκαστικά